Conflitos organizacionais : estudo de caso no Hospital Universitário Cassiano Antonio Moraes-HUCAM - Gaick, Valcerli Germano (2015)
The organizational climate is well cultivated can be an excellent management tool aimed at the conflict in the company. But if relegated to relational forces and environmental pressures, can cause harmful consequences to organizations. Against this backdrop, this research seeks to clarify the following research problem: What are the main conflicts in University Hospitals and what means are most likely to your management? Thus, it was defined as a general purpose survey and describe the main conflicts at the University Hospital Cassiano Antonio Moraes, in the administrative segment. As a consequence were established some specific objectives, which are: raise in the perception of administrative staff, which are the main focus of conflict; to map these conflicts and their sectoral relations; identify more appropriate conflict management techniques to situations encountered; present intervention proposal in the hospital segment. The study was limited to the hospital administrative area (warehouse, financial, purchasing and contracts) because it is an area in which interrelate professionals from various segments, which may have consequences throughout the Hucam. The research, initially quantitative, was complemented with qualitative data analysis. The research instruments were the questionnaire, the free interview and observation. The data were analyzed by means of statistical and later qualitatively, aided by respondents' answers and the field notes. In all 38 participating servers representing the target population. Statistical results did not generate clear results of conflicts, depending on the variation of responses from each sector. Qualitative analysis revealed that only two of the participants relate harmoniously with peers. The remaining 36 servers showed potential internal to the group and intergroup conflict. The main problems identified relate to values, lack of knowledge of the work of colleagues, personality profile and interpersonal relationships.